If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 17y + -4 = 8y + 61 + -6y Reorder the terms: 5 + -4 + 17y = 8y + 61 + -6y Combine like terms: 5 + -4 = 1 1 + 17y = 8y + 61 + -6y Reorder the terms: 1 + 17y = 61 + 8y + -6y Combine like terms: 8y + -6y = 2y 1 + 17y = 61 + 2y Solving 1 + 17y = 61 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 1 + 17y + -2y = 61 + 2y + -2y Combine like terms: 17y + -2y = 15y 1 + 15y = 61 + 2y + -2y Combine like terms: 2y + -2y = 0 1 + 15y = 61 + 0 1 + 15y = 61 Add '-1' to each side of the equation. 1 + -1 + 15y = 61 + -1 Combine like terms: 1 + -1 = 0 0 + 15y = 61 + -1 15y = 61 + -1 Combine like terms: 61 + -1 = 60 15y = 60 Divide each side by '15'. y = 4 Simplifying y = 4
| 29x-30=28x+38 | | x-2/3=x/6 | | 0.8(x+10)+0.4x=44 | | .25+6=2 | | 2x=w(5y-11)solvey | | 2y=w(5x-11) | | 26z+9=37 | | 53x-4=100 | | X^2-x=600 | | 5u-4/3+5u-4/6 | | -8/(-2)(4) | | 11(t-3)+4t=5(3t+3)-9 | | 5x+2=2x^2 | | -4(x+3)=2(x-12) | | -18x+8y-7=5 | | 4(t+5)-3=6t+13 | | 5(4+k)+3(2k-7)= | | 5x^2+16x-15=0 | | 6m+5=13+4m | | (5)+(14)= | | 14ab-21ab^2= | | 5x-18-x-3= | | 2/7p=-4/3 | | (11b-1)-5(2b+3)=-5 | | 6x/14=4/6 | | 12(5-2)= | | x+3y=35 | | 9x+5x+2+7=3x+4+10x | | 4x-60=6x | | 2/5x-9/25x=5 | | 5x+8=2x-14 | | 1/2(10x-1)=8 |